2018
DOI: 10.1021/acs.nanolett.8b00475
|View full text |Cite
|
Sign up to set email alerts
|

Active Tuning of Spontaneous Emission by Mie-Resonant Dielectric Metasurfaces

Abstract: Mie-resonant dielectric metasurfaces offer comprehensive opportunities for the manipulation of light fields with high efficiency. Additionally, various strategies for the dynamic tuning of the optical response of such metasurfaces were demonstrated, making them important candidates for reconfigurable optical devices. However, dynamic control of the light-emission properties of active Mie-resonant dielectric metasurfaces by an external control parameter has not been demonstrated so far. Here, we experimentally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
120
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(128 citation statements)
references
References 43 publications
2
120
0
Order By: Relevance
“…Later, Komar et al demonstrate electrical tuning of the transmission with similar structures, in which a voltage of 70 V is used to obtain a modulation depth of 75%. More recently, LCs are also used for beam‐steering and controlling the spontaneous emission in Mie‐resonant dielectric metasurfaces . Controlling the efficiency of diffraction into certain orders is realized by a spatially varying silicon nanodisk array infiltrated with LCs .…”
Section: Tuning Via Phase Transitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Komar et al demonstrate electrical tuning of the transmission with similar structures, in which a voltage of 70 V is used to obtain a modulation depth of 75%. More recently, LCs are also used for beam‐steering and controlling the spontaneous emission in Mie‐resonant dielectric metasurfaces . Controlling the efficiency of diffraction into certain orders is realized by a spatially varying silicon nanodisk array infiltrated with LCs .…”
Section: Tuning Via Phase Transitionsmentioning
confidence: 99%
“…The input laser beam can be deflected to 12° with an efficiency of 50% by heating the sample. Moreover, Bohn et al fabricate a silicon nanodisk array on the top of a fluorescent substrate, as shown in Figure c . By properly controlling the temperature of the LCs, the emission intensity doubles at the wavelength of 900 nm.…”
Section: Tuning Via Phase Transitionsmentioning
confidence: 99%
“…This allowed switching between two different modes by simply setting the polarization with the alignment of the LC layer. In other studies, liquid crystals have been used to actively enhance the nonlinear response of a metasurface and more recently for active control of spontaneous emission from a fluorescent substrate …”
Section: Adaptive Metasurfacesmentioning
confidence: 99%
“…All‐dielectric metasurfaces, in particular, which are composed of elements made of a high‐refractive index dielectric material, have been lately attracting more attention, as they show a very high diversity of exploitable properties, while being free from ohmic losses associated with the presence of metals . The potential of dielectric metasurfaces as a platform for low‐loss, compact, functional components has been extensively demonstrated in numerous applications, such as reflection/refraction control and wave‐front shaping, lensing, control of light emission or photoluminescence, polarization control and polarimetry, generation of vortex beams, highly selective filtering, or enhancement of nonlinear processes …”
Section: Introductionmentioning
confidence: 99%